Daya racun ekstrak kasar daun bintaro (Cerbera odollam Gaertn.) terhadap larva Spodoptera litura fabricius - Sri Utami; Lailan Syaufina; Noor Farikhah Haneda (Jurnal Ilmu Pertanian Indonesia, 2010)
Spodoptera litura Fabricius is one of polyphagous insects that often attacks so many plant species either annual and perennial crops. Severe infestation of the pest may decrease crop production. The farmers who grow agricultural crops generally control the insect pest using synthetic chemical insecticides. However, improper use of such pesticides may cause negative impacts to the environment. Insect pest control using botanical insecticide is an alternative which is relatively safe to the environment. A research to test the lethal effect of crude extract of bintaro leaf ( Cerbera odollam gaertn.) to S. litura larvae was conducted. The research was conducted at the laboratory of Forest Product Chemistry and the laboratory of Forest Entomology, Faculty of Forestry, IPB in 2009. The results shows that the crude extract of bintaro leaf has a strong knock down effect to S. litura larvae, with lC50 at 0,6 °/o to the second instar and 0,28 % to the second and the third instar. It is proven that the leaf extract, contains active chemical compounds pesticidal, e.g. flavonoid, steroid, saponin and tannin. Further tests are suggested under field condition researches should be conducted to test the efficacy of the extract in controlling S. litura at the nursery and the field.